Impact of the Global Financial Crisis and the Tunisia’s Jasmine Revolution on the Corporate Capital Structure: Evidence from Four Arab Countries - Hamouda, Raja Zekri Ben; Jilani, Faouzi (International Journal of Economics and Financial Issues, 2023)
This paper provides new evidence on capital structure determinants in the Arab world with special focus on the impact of the 2008 global financial crisis and the Jasmine Revolution on four different corporate leverage ratios. The sample consists of 440 non-financial listed companies from four Arab- Mediterranean countries (Egypt, Jordan Morocco and Tunisia) and the panel data are analyzed from the period 2003–2019. Statistical analysis of results are carried out by using the ordinary least squares ; three dummy variables are included (time, country and industry). The results indicate cross-country variations in four different leverage ratios. Moroccan firms, contrary to those in Tunisia and Jordan, show lower leverage ratios. By contrast, they report higher levels of « size », « profitability » and « growth opportunities ». The results also show that the Jasmine Revolution as well as the 2008 global financial crisis affects the impact of firm-specific determinants : After crisis and Jasmine Revolution, the positive and the negative effects of « size » and « profitability », respectively, become more important. Profitability is the most significant explanatory factor of corporate capital structure in Arab countries. During the two sub-periods, the growth opportunities and their negative impact on the corporate financial decisions depend on the choice of the leverage ratio (total debt versus long term debt – book values versus market values). Asset tangibility is the most critical factor : its positive effect on capital structure is more important before the Jasmine revolution and/or the global financial crisis. The effect is initially positive but becomes negative when leverage ratio is calculated using total values of debt (book and market values of debt). Results on capital structure determinants in the Arabic context not depend only on the choice of the leverage ratio, but also on the period considered.